Parametric Modeling of Part and Component in Cartesian Transfer Robot based on CATIA - Tian Yuan; Ping Xueliang; Hao Kaiqiang; Jiang Yi; Chen Hong (Jixie chuandong)
Based on four degrees of freedom cartesian transfer robot structural model,the method of parametric modeling of the main part and component of the cartesian robot are studied.Considering the actual needs of different production lines,and combined with CATIA virtual design technology and knowledge engineering techniques,the issues of cartesian robot three-dimensional model rapid generation is solved.The three-dimensional standard part and component library is built by CATIA V5R19.The selection of components and automatic generation are achieved,the designer can obtain the structural parameters by considering the user requirements and do some design calculations relevant to the selected design parameter.